Hysteroscopy to identify retained placental tissue and excision in secondary post-partum haemorrhage - Devabhaktuni, Pratibha; Allani, Padmaja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Most cases of secondary postpartum haemorrhage (PPH) are due to retained placental products (RPP). This study had a crop of five cases of secondary PPH, referral cases, during a period of six months during 2006. Four cases were following a caesarean delivery and in one, sub mucous and intra mural, uterine fibroids, caused retained placental tissue by distortion of the uterine cavity. Objectives of this study were to evaluate the feasibility of hysteroscopy to identify the retained placental products in cases of secondary postpartum haemorrhage. Verification of complete removal of RPP by reinsertion of hysteroscope, after removal of RPP by using a sponge holder, or curette. Methods: Trans vaginal ultrasonography (TVS) identified echogenic retained products of conception in all cases. Surgical profile investigations were done as per protocol. Transfusion of blood products was needed in some. Bettocchi 5 mm continuous flow hysteroscope (Karl Storz) was used. Storz endomat hysteroflator was used for irrigation and aspiration. Results: Hysteroscopic guided excision of the placental tissue was one-time treatment in four of study cases, and one needed a second hysteroscopic excision. Secondary PPH occurred at varying periods after the caesarean delivery, one week in one, two weeks in one case, three weeks in two cases and one woman was admitted with retained placenta, primary PPH continuing to secondary PPH. Hysteroscopy done during the puerperal period, in cases of secondary PPH, had certain challenges to cope with. Conclusions: Hysteroscopic guided excision of the retained placental tissue was successful in all the five cases with secondary postpartum haemorrhage. Hysteroscopy is an excellent procedure in cases of secondary PPH. We request guidelines committees to consider including hysteroscopic guided removal of retained placental products, in the algorithm of management of secondary PPH.